1991
DOI: 10.1111/j.1540-8159.1991.tb02864.x
|View full text |Cite
|
Sign up to set email alerts
|

Complications Associated with Retained Pacemaker Leads

Abstract: Retention of functionless pacemaker leads may occur following mechanical or infective problems (potentially or definitely infected) or after electrical failure of the lead. One hundred nineteen patients with a pacemaker lead (or leads) retained between 1970 and 1990 were reviewed retrospectively. Lead retention after an intervention dictated by potential or definite infection of the pacing system resulted in complications in 27 of 53 patients (51%), which in 22 patients (42%) were major (septicemia, superior v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 10 publications
0
23
0
1
Order By: Relevance
“…Several studies have shown a reinfection rate of 50% in retained transvenous leads after device infection. 28,29 Therefore, the American Heart Association (AHA) Scientific Statement recommends removal of all hardware (including epicardial leads) based on several studies. [30][31][32] However, none of these studies specifically investigated epicardial leads.…”
Section: Lead Performance and Durabilitymentioning
confidence: 99%
“…Several studies have shown a reinfection rate of 50% in retained transvenous leads after device infection. 28,29 Therefore, the American Heart Association (AHA) Scientific Statement recommends removal of all hardware (including epicardial leads) based on several studies. [30][31][32] However, none of these studies specifically investigated epicardial leads.…”
Section: Lead Performance and Durabilitymentioning
confidence: 99%
“…68 Data regarding the risk of CIED infection in patients with abandoned leads have failed to demonstrate an increased risk of device-related infection but are limited by small sample size and abbreviated follow-up periods. 27,30,46,48,51 In young patients with abandoned leads, Silvetti and Drago 27 observed an alarming 11% incidence of CIED infection compared with a 2% incidence in all pacemaker patients, although the trial was underpowered to reach statistical significance. All patients with CIED infection required definitive treatment with lead removal.…”
Section: Infectionmentioning
confidence: 99%
“…Moreover, most extraction experts would agree that the irrefutable risks of pacemaker and/or defibrillator lead abandonment are related to the potential need for future extraction-a risk that is essentially ignored despite the frequent need for transvenous or surgical extraction in the patients with complications of abandoned leads (29% to 100% of abandoned leads with complications). 27,46,47,50,51 There is not only a potential need for future extraction but also an increased risk of TLE, given the increase in lead burden, lead-lead binding, and implant duration in the time after the initial lead replacement. Thus, lead decisions at the time of system revision or upgrade must weigh the present risks of extraction with the future risks of both lead abandonment and potential lead extraction.…”
Section: Risk Versus Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, most authors agree upon the fact that local infection of the pacing system can cause successive serious complications such as septicemia, superior vena cava syndrome, and venous obstruction, and it is associated with a high rate of reinterventions (6,7). A conservative policy is often unsuccessful, and the total removal of leads is the most effective therapy.…”
Section: Introductionmentioning
confidence: 87%